MAFG‐AS1 promotes tumor progression via regulation of the HuR/PTBP1 axis in bladder urothelial carcinoma. Issue 8 (16th December 2020) - Xiao, Mengqing; Liu, Jianye; Xiang, Liang; Zhao, Kai; He, Dong; Zeng, Qinghai; Zhang, Qun; Xie, Dan; Deng, Minhua; Zhu, Yuxing; Zhang, Yeyu; Liu, Yan; et al.
Abstract: Long noncoding RNAs (lncRNAs) play a crucial role in progression of bladder urothelial carcinoma (BUC). However, the molecular mechanisms behind this role have not been elucidated yet. Here, we found that the lncRNA MAFG‐AS1, which is highly expressed in BUC, is correlated with aggressive characteristics and poor prognosis of BUC. We demonstrate that MAFG‐AS1 can promote BUC proliferation, invasion, metastasis, and epithelial‐mesenchymal transition in vitro and in vivo. Mechanistically, MAFG‐AS1 direct binding to Hu antigen R (HuR) could recruit ubiquitin‐specific proteinase 5 (USP5) to prevent HuR from degrading by ubiquitination. We further demonstrate that overexpression of MAFG‐AS1 can upregulate the expression of polypyrimidine tract‐binding protein 1 (PTBP1) through promoting its stability mediated by bound HuR. In conclusion, these findings indicate that MAFG‐AS1 promotes the progression of BUC via regulation of the HUR/PTBP1 axis. Targeting MAFG‐AS1 may provide a novel strategy for individualized therapy and a potential biomarker for prognosis of BUC. Abstract : Our findings indicate that MAFG‐AS1 acts as an oncogene to promote the progression of BUC via regulation of the HUR/PTBP1 axis. Targeting MAFG‐AS1 may provide a novel strategy for individualized therapy and a potential biomarker for prognosis of BUC